The legal recognition of the social economy in Europe: Scope and consequences - Fajardo García, Isabel Gemma (Cooperativismo & Desarrollo, 2019)
The concept of the social economy is found in the doctrine and public policies of the European Union and itsmember states since the eighties of the twentieth century. In 2009, the European Parliament urged the Statesto regulate the social economy, in order to make it visible and be able to draw up and apply promotion policies from both the European Union and the States. We have considered to what extent this recommendation of the European Parliament has been answered and we have analyzed the European legislations dictated around the social and solidarity economy, seeking to highlight its identity features such as, for example, the concept, the aims and the principles, as well as the models of the proposed company and the accreditation system of its status as a social economy company. From the analysis of the laws passed after 2009, it is concluded that, although there has been a legal recognition of the social economy, this has not been very widespread and, in addition, the advances in favor of its promotion have not been significant. On the one hand, the plurality of concepts that have been generated around the social economy (solidarity economy, collaborative economy, social enterprise, social entrepreneurship) are creating confusion about its concept and scope.
Keywords: social economy; solidarity economy; social enterprise; Europe; legislation